Russian Federation : Staff Report for the 2001 Article IV Consultation and Post-Program Monitoring Discussions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses the Russian Federation's 2001 Article IV Consultation and Post-Program Monitoring Discussions. Improved economic performance and reduced external vulnerability were reflected in a strengthening of financial market indicators in 2001. The Russian stock market doubled in U.S. dollar terms, bond spreads narrowed significantly, and rating agencies upgraded Russia's debt. The near- to medium-term outlook remains favorable. The recent successes in building up strong external and fiscal positions should enable Russia to deal with the current less favorable external environment with the prevailing policy framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet